Refleksi Filosofis Tantangan Pendidikan Islam Modern Perspektif Ikhwan As-Shafa - Arzaqi, Argha Zidan; Rohmah, Binti Miftakul; Aisyah, Siti (Comprehensive Journal of Islamic Studies, 2025)
This study examines the thoughts of Ikhwan Shafa in the context of Islamic education and its relevance to the challenges of modern education. This study uses a descriptive qualitative methodology to examine the holistic educational philosophy of Ikhwan Shafa which emphasizes the integration of religious knowledge and general knowledge, as well as the development of students' character and morals. The results of the study indicate that the educational philosophy of Ikhwan Shafa is very much in line with the needs of current Islamic education, especially in terms of developing individuals with high morals and being able to maintain harmonious relationships with God, others, and nature. The proposed curriculum includes religious knowledge and general knowledge, and its learning methods are from concrete to abstract, which is in line with Indonesian Islamic education standards. These findings have important implications for the development of Islamic education curricula and methods that balance spiritual values ​​and intellectual abilities in the modern era.